2020
DOI: 10.1186/s12943-020-01191-9
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0020710 drives tumor progression and immune evasion by regulating the miR-370-3p/CXCL12 axis in melanoma

Abstract: Background Circular RNAs (circRNAs) have been reported to have critical regulatory roles in tumor biology. However, their contribution to melanoma remains largely unknown. Methods CircRNAs derived from oncogene CD151 were detected and verified by analyzing a large number of melanoma samples through quantitative real-time polymerase chain reaction (qRT-PCR). Melanoma cells were stably transfected with lentiviruses using circ_0020710 interference or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 35 publications
1
93
0
Order By: Relevance
“…Elevated circ_0020710 was observed in melanoma tissues. It promoted cell proliferation, migration, and invasion in vitro and tumor growth in vivo via the miR-370-3p/CXCL12 axis [114] ( Table 1). The roles of circRNAs in CXCR4/ CXCL12-mediated distant metastasis are depicted in Fig.…”
Section: Exosomal Circrnas Affect Tumor Homingmentioning
confidence: 99%
“…Elevated circ_0020710 was observed in melanoma tissues. It promoted cell proliferation, migration, and invasion in vitro and tumor growth in vivo via the miR-370-3p/CXCL12 axis [114] ( Table 1). The roles of circRNAs in CXCR4/ CXCL12-mediated distant metastasis are depicted in Fig.…”
Section: Exosomal Circrnas Affect Tumor Homingmentioning
confidence: 99%
“…Red and blue color indicated the oncogenic and suppressive functions of circRNAs in different biological processes involved in melanoma progression, respectively. Up and down arrows indicated the activation and inhibition of physiological processes in melanoma pathogenesis, respectively (Bian et al, 2018 ; Ju et al, 2018 ; Luan et al, 2018 ; Wang Q. et al, 2018 ; Lin et al, 2019 ; Shang et al, 2019 ; Zou et al, 2019 ; Chen J. et al, 2020 ; Chen Z. et al, 2020 ; Hanniford et al, 2020 ; Jin et al, 2020 ; Lu and Li, 2020 ; Lu et al, 2020 ; Qian et al, 2020 ; Tian et al, 2020 ; Wei et al, 2020 ; Liu et al, 2021 ; Yin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that mir-144 regulated MAPK signaling pathway factors, such as DUSP5 and TGFBR1 (Qian et al, 2020 ). Other circRNAs which also acted as oncogene and miRNA sponge in melanoma included circ_0025039 (Bian et al, 2018 ), circ_0016418 (Zou et al, 2019 ; Lu et al, 2020 ), circ_0020710 (circ-CD151) (Wei et al, 2020 ), circ_0079593 (Lu and Li, 2020 ), circ_0001591 (Yin et al, 2021 ), and circ_0119872 (Liu et al, 2021 ). Specific miRNA targets and downstream molecules are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, circRNA circ_0020710 drives tumor progression and immune evasion by regulating the miR-370-3p/CXCL12 axis in melanoma. 8 CircRNA hsa_circRNA_101996 increases cervical cancer proliferation and invasion through activating TPX2 expression by restraining miR-8075. 9 CircRNA hsa_circRNA_100290 serves as a ceRNA for miR-378a to regulate oral squamous cell carcinoma cell growth via Glucose transporter-1 (GLUT1) and glycolysis.…”
Section: Introductionmentioning
confidence: 99%